2010
DOI: 10.1002/poc.1798
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of color change and photocyclization of diarylethene with metal complex

Abstract: Modulation of color change and photocyclization of diarylethene with metal complex is described. A diarylethene derivative with 4‐(ethylideneamino) phenol group 1a is prepared and photochromic behavior is investigated. It is found that 1a exhibits ring‐opening and ring‐closing photoisomerization with UV/Vis light irradiation in solution. Addition of Cu(OAc)2 to the solution of 1a produces a metal complex 1a–Cu, which generates not only marked color change but also significant promotion in photocyclization. Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The focus has been on the influence of electron‐withdrawing groups, such as fluorine or chlorine atoms, and they observed that these halide substituents and their positions have a significant effect on the properties of the diarylethene compounds. A more recent study reports that the presence of phenol groups in the diheteroarylethenes produces a metal complex with Cu 2+ and other divalent metals, which generates not only a marked color change in the spectra (red displacement) of the closed isomer, but also significant promotion of photocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…The focus has been on the influence of electron‐withdrawing groups, such as fluorine or chlorine atoms, and they observed that these halide substituents and their positions have a significant effect on the properties of the diarylethene compounds. A more recent study reports that the presence of phenol groups in the diheteroarylethenes produces a metal complex with Cu 2+ and other divalent metals, which generates not only a marked color change in the spectra (red displacement) of the closed isomer, but also significant promotion of photocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…They can provide new properties deriving from the combination of redox, optical, and magnetic properties of the metal complexes. Through combining a photochromic moiety with an organometallic compound, the photochromic properties could be simply modulated by different coordinating metal centers . In addition, the metal terpyridine (TPY) complexes have excellent stability and remarkably high binding affinity towards transition metal ions, showing photophysical/photochemical properties, which have led to the development of various luminescent metal compounds and sensitizers for photovoltaic devices .…”
Section: Introductionmentioning
confidence: 99%